Immediate-Release Nifedipine Binary Dry Powder Mixtures with Nanocellulose Featuring Enhanced Solubility and Dissolution Rate - Athanasios Mantas; Albert Mihranyan (MDPI AG, 2019)
Nifedipine (NIF) is a 1,4-dihydropyridine-based calcium channel blocker with poor solubility, whose bioavailability is highly dependent on the type of formulation. Dry powder mixtures of 20% w/w NIF with microcrystalline cellulose (MCC) and its high surface area nanocellulose analogue, which is namely Cladophora (CLAD) cellulose, were produced by heating at the melting temperature of the drug for 1 h. Non-heated samples were used as a reference. The solid-state properties of the mixtures were characterized by scanning electron microscopy, differential scanning calorimetry and X-ray diffraction. The drug release was studied in biorelevant media, including simulated gastric fluid (SGF), fasted-state simulated intestinal fluid (FaSIF) and fed-state simulated intestinal fluid (FeSIF). An enhanced apparent solubility and faster dissolution rate of NIF were observed in the heated mixture of NIF with CLAD-H in all tested biorelevant media (i.e., SGF, FaSIF and FeSIF), which was due to NIF amorphization in the high surface area nanocellulose powder. Ordinary MCC, which is essentially non-porous, did not produce an enhancement of a similar magnitude. The results of the study suggest that dry powder formulation using high surface area nanocellulose is a facile new strategy for formulating calcium channel blocker drugs, which could potentially be a viable alternative to currently used soft gel liquid capsules.